Unlocking the full potential of open innovation in the life sciences through a classification system. Issue 4 (April 2018) - Nilsson, Niclas; Minssen, Timo
Highlights: The actual meaning and implementation of Open Innovation varies to a great extent. A common Open Innovation terminology from a life science perspective is outlined. Proposal to use a 5-level classification system reflecting the degree of openness. Abstract : A common understanding of expectations and requirements is critical for boosting research-driven business opportunities in open innovation (OI) settings. Transparent communication requires common definitions and standards for OI to align the expectations of both parties. Here, we suggest a five-level classification system for OI models, reflecting the degree of openness. The aim of this classification system is to reduce contract negotiation complexity and times between two parties looking to engage in OI. Systematizing definitions and contractual terms for OI in the life sciences helps to reduce entry barriers and boosts collaborative value generation. By providing a contractual framework with predefined rules, science will be allowed to move more freely, thus maximizing the potential of OI.